Finding oneself in the other - Cohen, G. A. (Gerald Allan), 1941-2009 (Princeton University Press, 2012)
This is the second of three volumes of posthumously collected writings of G.A. Cohen, who was one of the leading, and most progressive, figures in contemporary political philosophy. This volume brings together some of Cohen's most personal philosophical and nonphilosophical essays, many of them previously unpublished. Rich in first-person narration, insight, and humor, these pieces vividly demonstrate why Thomas Nagel described Cohen as a ""wonderful raconteur."" The nonphilosophical highlight of the book is Cohen's remarkable account of his first trip to India, which includes unforgettable vignettes of encounters with strangers and reflections on poverty and begging.